Alguns aspectos da análise dinâmica de estruturas offshore - Sequera, Carlos Eduardo Genatios (1981)
The present work deals with the Deterministic Dynamic Analysis of Offshore Structures, by the: - Frequency Response Method; - Direct Integration Method. A study was done trying to identify the basic problems in order to make certain simplifications. These producted a better computacional efficiency. A computational prograrn was developed for the Frequency Response Analysis, it included certain idealizations whose effects were also studied. At the same time a prograrn for the Direct Integration Analysis was also developed in order to compare the results. Using these programs a group of typical structures were analysed. The results and conclusions are presented at the end.